PENGENALAN MANAJEMEN BISNIS SYARIAH MELALUI PEMBERDAYAAN IBU-IBU DI DESA CIMANGGU I KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR - Nia Oktaviani; Ujang Buchori Muslim; Hasbi Ash Shiddieqy (Jurnal Pengabdian Kepada Masyarakat Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2021)
Abstract The program is a community empowerment activity that has the aim of prospering the community by utilizing existing natural resources, then processing them so that they can help the community's economy during the Covid-19 pandemic. Cimanggu Satu Village, with most of the community being farmers, inspired students and lecturers to process agricultural products. One of them is by processing the abundant spinach vegetables into chips and spinach sticks so that they can have a higher selling power than just selling the vegetables. The business that will be developed first is developed through the development of human resources (HR) through outreach activities to PKK mothers. By empowering PKK women in Cimanggu Satu Village to develop businesses, it is hoped that they can help the community's economy during the Covid-19 pandemic and can become community creations and innovations to open up business opportunities. Keywords: Empowerment of PKK mothers, Counseling of spinach chips and sticks, Family income